Reducing Structural Complexity of Software by Data Streams - Kollár, Ján; Wassermann, L’Ubomír; Vranic, Valentino; Vagac, Michal (INFOCOMP Journal of Computer Science, 2009)
Language architecture is developed from context-free grammar enriched by communication channels. Four types of formal communication channels and one type of informal communication channel are identified for functional languages, to provide a systematic background for human-machine communication. Formal channel positions are determined by a grammar, and informal channels by a programmer. Structural complexity is radically decreased since data streams are approximately as concise as computer machine code, but they are semantically equivalent to high level functional programs. Using simple example of a functional language, we present the principle of functional language architecture and its driving by a data stream. In particular, we show how a program is initially recorded, how it is automatically generated, and how it is adapted to verbose, quiet and collaborative modes. As a result, we propose data stream-oriented architecture, in which structural complexity of current programs is rapidly decreased, since the execution of language architecture machine code means the execution of high-level programs.